DELIBERASI DALAM PEMBANGUNAN DESA RENAK DUNGUN KECAMATAN PULAU MERBAU KABUPATEN KEPULAUAN MERANTI TAHUN 2014-2015 - Rafi, M.; Wicaksono, Baskoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was motivated by the village development planning which is a deliberative democratic processes and institutions in the village. but in actual experience various problems, such as attendance musrenbangdes dominated by the village government, and the proposed development of communities in rural development planning meetings were not accommodated and realized according to the wishes and expectations of society. This study aims to determine the deliberation of interest in rural development planning and deliberation impact on rural development. The method used in this research is method descriptive approach to qualitative research. Type of research data is primary data and secondary data. Data collection techniques in this study were interviews and documentation. Technical analysis of the data used is descriptive qualitative data analysis.The results showed that the deliberation of interest in rural development planning is still not going well. In addition deliberation in rural development are still not able to have a significant impact. It can be seen from some of the data obtained from the Village, District, as well as the field data collected. The right solution to overcome these problems is the village government should encourage and increase community involvement in the process of deliberation on interest in the development plan of the village, and the village government should cooperate with existing institutions in villages to create a better deliberations.Keywords : Deliberation, Village Development